INTERACTION BETWEEN MYCOBACTERIA AND MACROPHAGES THROUGH THE COMPLEMENT SYSTEM - MANIVANNAN S; V NARAYAN RAO; RAMANATHAN VD (International Journal of Pharma and Bio Sciences, 2014)
Mycobacterium tuberculosis remains one of the most common causes of infectious disease morbidity worldwide. During the initial interaction with human host, M. tuberculosis uses macrophages as its primary host cell for survival and replication, which implies that this macrophage invasion by the mycobacteria is one of the critical aspects in establishing tuberculosis infection. Needless to say, M. tuberculosis has also identified numerous portals of entry for parasitizing macrophages, which include macrophage receptors that can recognize and bind to the bacilli. Besides this, the complement system, belonging to both innate and adaptive components of immune system and which is made up of more than 35 proteins, also contributes to the interaction between macrophages and mycobacteria. M. tuberculosis can bind to complement receptors via both complement-dependent and independent pathways. Complement component C3 identified as the major component in human serum is involved in enhancing the adherence and uptake of M. tuberculosis by mononuclear phagocytes. This review focuses mainly on the interaction of complement system and mycobacteria. Complement and adaptive immunity includes B-cell and T-cell mediated immunity, apoptosis, cytokine production, granuloma formation and immune regulation. The initial interaction on macrophage and mycobacteria will help delineate the contribution of this early host–pathogen interaction to the pathogenesis of tuberculosis.